Naturally Assembled Excimers in Xanthenes as Singular and Highly Efficient Laser Dyes in Liquid and Solid Media - Cerdán, Luis; Martinez-Martinez, Virginia; García-Moreno, Inmaculada; Costela, Angel; Perez-Ojeda Rodriguez, Maria Eugenia; Lopez-Arbeloa, Iñigo; Burgess, Kevin; Wu, L.X. (Advanced Optical Materials, 2013)
Herein, for the first time, outstanding laser performance is demonstrated in liquid solution and solid state by naturally assembling excimers of organic fluorophores (rosamine dyes). Highly efficient and photostable laser dye properties, with broadened tunability covering 80 nm in the red spectral region (590-670 nm), is attributed to the coexistence of monomers and excimers induced under high optical gain conditions. Amplified spontaneous emission measurements in rosamine-doped polymer thin films show that the excimer exhibits a threshold lower and a gain higher than those corresponding to the monomer species. These laser properties make rosamines excellent candidates for biophotonic and spectroscopic applications, overcoming the main drawbacks exhibited by other long-wavelength (>600 nm) laser dyes, including low absorption at the standard pump wavelength (532 nm), low laser efficiency, and poor chemo-and photostability.